Factors that Account for Good Academic Performance among Children from Single-Parent Homes of Adventist Senior High School, Kumasi, Ghana - Boampong, Lydia; Torsu, Leonard Atsu (International Journal of Applied Research and Sustainable Sciences, 2024)
Literature on the factors that account for good academic performance among children from single-parent homes remains scarce. This study examined the factors that account for good academic performance among children from single-parent homes at Adventist Senior High School in Bantama, Kumasi. The study adopted the qualitative approach and the case study design. Ten teachers, ten single parents, and ten students from single-parent homes were purposively sampled and interviewed. The data was analyzed using thematic analysis. Within the frame of Cognitive Development Theory and John Bowlby’s Attachment Theory, the findings revealed that single parents play roles by visiting their children in school, providing them with educational needs, advising their children, and arranging extra classes for their children to enhance their academic performance. It was also revealed that teachers provided counseling services to students and encouraged and motivated them to learn. Findings also show that environmental factors, social media, and students' IQ levels are other factors accounting for the good academic performance of students from single-parent homes. The study concludes that apart from the significant role of teachers, environmental factors, students' IQ level, and social media, single parents can push their children to perform well in school when they are financially capable and well-determined. The study recommends that single parents participate in school committee activities that are more concerned with their children's academic well-being than other school development initiatives. We also recommend that single parents provide their children with smartphones so they can benefit from social media and improve their studies.